Enhanced Production of Acarbose and Concurrently Reduced Formation of Impurity C by Addition of Validamine in Fermentation of Actinoplanes utahensis ZJB-08196 - Xue, Ya-Ping (Hindawi Publishing Corporation, 2013)
Commercial production of acarbose is exclusively via done microbial fermentation with strains from the genera of Actinoplanes. The addition of C(7)N-aminocyclitols for enhanced production of acarbose and concurrently reduced formation of impurity C by cultivation of A. utahensis ZJB-08196 in 500-mL shake flasks was investigated, and validamine was found to be the most effective strategy. Under the optimal conditions of validamine addition, acarbose titer was increased from 3560 ± 128 mg/L to 4950 ± 156 mg/L, and impurity C concentration was concurrently decreased from 289 ± 24 mg/L to 107 ± 29 mg/L in batch fermentation after 168 h of cultivation. A further fed-batch experiment coupled with the addition of validamine (20 mg/L) in the fermentation medium prior to inoculation was designed to enhance the production of acarbose. When twice feedings of a mixture of 6 g/L glucose, 14 g/L maltose, and 9 g/L soybean flour were performed at 72 h and 96 h, acarbose titer reached 6606 ± 103 mg/L and impurity C concentration was only 212 ± 12 mg/L at 168 h of cultivation. Acarbose titer and proportion of acarbose/impurity C increased by 85.6% and 152.9% when compared with control experiments. This work demonstrates for the first time that validamine addition is a simple and effective strategy for increasing acarbose production and reducing impurity C formation.